Gas evolution in electrochemical flow cell reactors induces resistance gradients with consequences for the positioning of the reference electrode. Issue 45 (20th August 2021) - Jännsch, Yannick; Hämmerle, Martin; Leung, Jane J.; Simon, Elfriede; Fleischer, Maximilian; Moos, Ralf
Abstract : The gas evolution during electrolysis in flow cells results in inhomogeneous distributions of resistance, current and voltage along the flow axis. Abstract : With the transfer of the electrochemical CO2 -reduction from academic labs towards industrial application, one major factor is the increase in current density. This can be achieved via the usage of a gas diffusion electrode. It allows for electrochemical reactions at the three-phase boundary between gaseous CO2, liquid electrolyte and electrocatalyst. Thus, current densities in commercially relevant magnitudes of 200 mA cm −2 and beyond can be reached. However, when increasing the current density one faces a new set of challenges, unknown from low current experiments. Here, we address the issue of gas evolution causing a local increase in resistance and the impact on the operation of flow cells with gas diffusion electrodes. We set up a simple simulation model and compared the results with experiments on a real setup. As a result, the gas evolution's strong impact on current-, potential- and resistance-distributions along the flow axis can be described. Main consequence is that the positioning of the reference electrode has a significant effect on the locally measured IR-drop and thus on the measured or applied potential. Therefore, data from different setups must be compared with great care, especially with respect to the potentials, on which the cell is operated.